Synthesis and Characterization of Some Metal Complexes of Cu(II), Cd(II), UO2(II) and Pd(II) with Anthracene Carboxaldehyde Semicarbazone - Marykutty, P.V.; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
The metal complexes of the type [CuL2(H2O)2), UO2L2,PdL2 and CdL2 where L = anthracene carboxaldehyde semicarbazone are synthesised. The IR spectral data suggest the coordination of ligand through O and N atom. The analytical, electronic, spectral and magnetic data further confirm the geometry of the complexes.